Heterotopic pregnancy: Diagnosis and pitfall in ultrasonography - Achmad Kemal Harzif; Purnomo Hyaswicaksono; Riyan Hari Kurniawan; Budi Wiweko (Wolters Kluwer Medknow Publications, 2021)
Heterotopic pregnancy (HP) is the coexistence of extrauterine and intrauterine pregnancies. This case is rare, difficult to diagnose, and threatening if left untreated. Incidental rate is estimated 1 in 30,000 spontaneous pregnancies and higher in assisted reproductive techniques. HP is often missed because of the detection of intrauterine sacs; therefore, comprehensive and systematic ultrasonography (USG) is needed, especially when there is ectopic pregnancy suspicion or when there is free fluid in the pelvis. A 46-year nulligravida with 13-year primary infertility history underwent frozen embryo transfer process with positive beta-human chorionic gonadotropin 2 weeks after the procedure. Clinical pregnancy is expressed by gestational sac findings at 6-week gestation. Two weeks later, she complained of lower right abdominal pain accompanied by spots from the birth canal. USG showed intrauterine pregnancy and sac appropriate to 8-week gestation and adnexal mass accompanied by a ring of fire image. The patient underwent right salpingectomy, recovered well, and continued her pregnancy. In vitro fertilization is the main risk factor for multiple and ectopic pregnancies. Clinical manifestations are similar to pregnancy loss or ectopic pregnancy. Specific risk factor must be acknowledged by the physician prior initial examination to rule out HP. Transvaginal ultrasound is useful in making the diagnosis of HP, especially in early pregnancy.